O DIREITO DO USO DO NOME PRÓPRIO NA TOPONÍMIA PORTUGUESA - Portela, Irene (European Scientific Journal, ESJ, 2014)
The misuse of the name and in consequence the violation of the right to use the name raises serious legal order and the protection and guarantee of legal certainty. This issue is particularly serious if it is the right to use the name on road signs and signage used to designate geographical locations. The misuse of the English language can not excuse himself from behind the agreement spelling 1990.